(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Proton pump inhibitors (PPIs) are in routine widely prescribed to hemodialysis patients. Recent studies have reported the association of PPIs use with hypomagnesemia in patients with long term hemodialysis. This study aims to determine the frequency of hypomagnesemia in patients of hemodialysis taking proton pump inhibitors. Patients and methods: This cross-sectional study was conducted in the Department of Nephrology of Sandman Provincial Hospital Quetta from 01-6-2019 till 01-9-2019. A total of 120 patients (52 PPI users and 68 non-PPI users) who were on HD for more than 06 months were included. Data regarding age, gender, duration of hemodialysis and taking PPIs were collected. Determination of serum magnesium was made by taking 3 different samples at 2 weeks’ interval and the mean value of serum magnesium was calculated. Serum Mg2+ levels <2.0 mg/dL was taken as hypomagnesemia. A Chi-square test was applied to determine the association of PPI use with hypomagnesemia. Results: Demographic variables such as age and gender were not significantly different between the groups. There was female dominance in both groups (73% in PPI groups and 66.1% in the non-PPI group (p-value 0.65). The mean duration of dialysis was 45.3±13.8 months in PPI users versus 48.9±12.9 months in non-PPI users (p-value 0.14). There was a significantly higher frequency of hypomagnesemia in PPI users; 36 (69.3%) versus 27 (39.7%) in non-PPI users (p-value 0.001). Conclusion: The use of PPI is associated with a significant reduction in serum magnesium levels. So serum magnesium levels should be advised as routine monitoring in patients of hemodialysis taking PPIs.